IMPLEMENTASI PERATURAN GUBERNUR PROVINSI DKI JAKARTA NOMOR 123 TAHUN 2014 TENTANG KEPESERTAAN DAN PELAYANAN JAMINAN KESEHATAN DI DKI JAKARTA - Veronica Widianti; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2017)
Health is an essential factor that potentially becomes a paramater of people’s welfare. Genuinely the health in Indonesia is still below par, one of the factors is the poverty. The Governor of DKI Jakarta constructed a regulation which is Gubernatorial Regulation No. 123 Of The Year Of 2014 about Membership and Service of Health Insurance to provide the access for the people of DKI Jakarta who have no health insurance and for the people live under poverty to obtain health insurance that is fully-funded by Regional Budegt (APBD) of DKI Jakarta Province. The objective of this research is to perceive the implementation of Gubernatorial Regulation No. 123 Of The Year Of 2014 about Membership and Service of Health Insurance in DKI Jakarta. In addition, it aims to perceive the supporting and afflicting factors of the regulation. This research utilized qualitative descriptive approach. The data in this research obtained from interviews with informant, observation, and document. Based on the result of the research, shown that the implementation had materialized well regarding the members and service given however there were found lack. The supporting factor of the implementation were the standards and regulations target, communication amidst the organizations and targetted communities, budget resource, characteristic of institutions as the actors and economic status. While the afflicting factors were the facility resource, human resource and political status. The suggestions are to add more officers and improve the service on first health facility and extended health facility and provide opportunity for government to generate service for existing member of health insurance in addition to the existing services.